Relationship of Nutritional Status and Development in Toddlers Aged 1-5 Years - Niken Grah Prihartanti; mudhawaroh mudhawaroh; Septi Fitrah (Institute of Computer Science (IOCS), 2022)
Development has successive stages starting from ability to do perfect things and each individual has a different pace of development. The acceleration and deceleration process can be influenced by several factors, namely hereditary factors, environment, nutrition, and others. This study used a correlation design with a cross sectional approach. The population is all stunting toddlers aged 1-5 years in Denanyar Village, Jombang Regency, with a simple random sampling technique obtained a sample of 30 respondents. Data were collected using Length/Age and KPSP observations and then analyzed using the Spearman Rank test. The results showed that most of the nutritional status of toddlers was normal nutrition as many as 18 respondents (60%). Most of the development of toddlers is according to their age as many as 25 respondents (83.3%). Based on the results of statistical tests obtained p value < α and contingency coefficient of 0.546 so it can be concluded that there is a strong relationship between nutritional status and the development of toddlers aged 1-5 years. From the results of this study it can be concluded that nutritional status will affect the development of toddlers. In the growth and development of children need nutrients so that the process of growth and development goes well